2018
DOI: 10.3389/fmicb.2018.01895
|View full text |Cite
|
Sign up to set email alerts
|

Primary Lung Dendritic Cell Cultures to Assess Efficacy of Spectinamide-1599 Against Intracellular Mycobacterium tuberculosis

Abstract: There is an urgent need to treat tuberculosis (TB) quickly, effectively and without side effects. Mycobacterium tuberculosis (Mtb), the causative organism of TB, can survive for long periods of time within macrophages and dendritic cells and these intracellular bacilli are difficult to eliminate with current drug regimens. It is well established that Mtb responds differentially to drug treatment depending on its extracellular and intracellular location and replicative state. In this study, we isolated and cult… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…The limited sampling schedule in this pilot study does not allow for estimation of pharmacokinetic parameters related to the rate of absorption of 1599 from the lungs and will be addressed in more detailed studies in the future. However, we could recently show that 1599 is readily taken up into murine lung derived dendritic cells and macrophage cell lines [9]. Based on the generally more rapid absorption into alveolar compared to epithelial cells and the overall ability of 1599 to be taken up into cells, the rapid pulmonary absorption rate of 1599 suggests that the drug is being delivered to the peripheral region of the lungs [10].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The limited sampling schedule in this pilot study does not allow for estimation of pharmacokinetic parameters related to the rate of absorption of 1599 from the lungs and will be addressed in more detailed studies in the future. However, we could recently show that 1599 is readily taken up into murine lung derived dendritic cells and macrophage cell lines [9]. Based on the generally more rapid absorption into alveolar compared to epithelial cells and the overall ability of 1599 to be taken up into cells, the rapid pulmonary absorption rate of 1599 suggests that the drug is being delivered to the peripheral region of the lungs [10].…”
Section: Resultsmentioning
confidence: 99%
“…In addition, the high drug concentration in the lungs also allows easier accessibility of 1599 to alveolar macrophages [11], which are the predominant form of infected cells in pulmonary tuberculosis. Although macrophage uptake of 1599 was found to be significantly higher than spectinomycin, the parent compound of 1599, and streptomycin, a second line anti-tuberculosis agent [9], creating high localized concentrations of the drug that can kill the intracellular Mtb is considered highly desirable in tuberculosis therapy [12].…”
Section: Resultsmentioning
confidence: 99%
“…Previously, it has been reported that gut microbiota affects host response to cancer therapies by modulating tumor-infiltrating myeloid cells [19,20]. Myeloid cells, such as DCs, are the key cells to mount innate immune response and activates T cells during Mtb infection [39,48,49]. This process requires efficient expression of MHC-II and costimulatory molecules such as CD86.…”
Section: Discussionmentioning
confidence: 99%
“…Another mechanism responsible for the observed PAE differences may potentially be related to differential interaction with phospholipids in the bacterial cell membrane, a feature compounds such as spectinamides as secondary amines are known to display (Hein et al, 1990). Drug uptake experiments in primary lung derived dendritic cells and macrophage cell lines indicate at least for 1599 good intracellular uptake (Santos et al, 2018), but similar experiments in Mycobacterium tuberculosis complex bacteria are so far unavailable. In conclusion, we characterized the anti-mycobacterial activity of spectinamide lead candidates by establishing dynamic kill curves in an in vitro PK/PD model, followed by a subsequent pharmacometric analysis.…”
Section: Discussionmentioning
confidence: 99%